Enhanced perpendicular magnetic anisotropy of ferrimagnetic Mn4N films deposited on the glass substrate. (7th July 2022) - Li, Wenchang; Xu, Xinxing; Gao, Tenghua; Harumoto, Takashi; Nakamura, Yoshio; Shi, Ji
Abstract: Mn4 N films have been prepared on the glass substrate by reactive magnetron sputtering, using Mn3 N2 as the seed layer. Compared with Mn4 N film directly grown on the glass substrate, the crystallinity and perpendicular magnetic anisotropy (PMA) of the Mn4 N film with the seed layer are significantly enhanced. By varying the thickness of the Mn3 N2 seed layer, the structural and magnetic properties are systematically investigated. It is shown that the seed layer thickness is pivotal in the growth of Mn4 N with good crystallinity. The crystallinity of Mn4 N first improves with the increase in the layer thickness of Mn3 N2, and degrades after an optimal thickness; this is related to the change in the surface roughness of the Mn3 N2 layers. The Mn3 N2 layer not only promotes the growth of Mn4 N film with c -axis orientation, but also provides additional N atoms to the growing surface to prevent Mn4 N from being oxidized. This simple method can be used to prepare high-quality Mn4 N films on a glass substrate, which show strong PMA and are suitable for spintronics applications.